MANAJEMEN PEMBINAAN DI PONDOK PESANTREN WALISONGO SUKAJADI LAMPUNG TENGAH - Ardi Pramana; Syukron Jazuli (Al-Mahabbah : Jurnal Manajemen Pendidikan Islam, 2025)
The Shohbah approach is an educational method rooted in the prophetic tradition of the Prophet Muhammad (peace be upon him), emphasizing emotional closeness, exemplary conduct, and the internalization of noble values. Within the pesantren (Islamic boarding school) context, this approach is considered effective in shaping students who are intellectually competent and morally and spiritually strong. This study aims to explore the character development management of students through the Shohbah approach at Pondok Pesantren Walisongo Sukajadi, Central Lampung. The research employed a qualitative approach with a case study design, using participatory observation, in-depth interviews, and documentation techniques. The findings reveal that character development through Shohbah includes deliberation forums (musyawarah), spiritual development, and involvement in social activities, all of which contribute to strengthening the students’ character. The impact is evident in the increased discipline, responsibility, social empathy, and both academic and interpersonal competencies of the students. The success of this approach is influenced by several factors, including the exemplary leadership of the pesantren caregivers, a supportive learning environment, and collaboration between the pesantren and students' families. The study concludes that the Shohbah approach is a relevant and contextual educational strategy for fostering the character of the younger generation in modern times and holds significant potential for application in various educational settings, both religious and general